Thermal Modification of Wood: Mechanisms, Property Changes, and Industrial Applications – A Review - Hasan, Omaima A; Hadi, Mohammed Jamal (American Journal of Botany and Bioengineering, 2026)
Heat treatments to modify wood have become an effective and green methodology of improving wood functionality without use of chemical preservatives. When timber is exposed to high temperatures under harshly regulated circumstances, some significant changes in the chemical and structural characteristics of cell wall polymers take place, leading to enhanced dimensional stability, reduced hygroscopicity, and increased biological longevity. The review summarises the principles, processes and mechanisms involved in thermal modification of wood, specifically the degradation of hemicellulose, alteration of cellulose crystallinity, condensation of lignin and the resulting degradation of hydroxyl functionalities. The effects of thermal modification on of physical and mechanical properties of wood are critically analysed and the effects include variations in density, moisture sorption kinetics, dimensional stability, colouration, thermal conductivity, and strength properties. Although timber treated using thermal treatment shows a high level of resistance to moisture ingress and biological decay, diminished mechanical strength and a higher level of brittleness have been identified as the main limitations thus limiting its use to non-structural cases mostly. The review also outlines the current industrial thermal modification technologies and outlines modern and future uses of thermally modified wood as an exterior and interior product, including cladding, decking, flooring, and furniture. Lastly, the article appraises the benefits and shortcomings of thermal modification in comparison to traditional forms of chemical and mechanical wood modification procedures, and suggests the future research directions intended towards optimising treatment regimes, retaining the strengths properties and enhancing the overall sustainability profile of thermally modified wood products. This literature review leads to the sophisticated perception of thermal modification as the key technology of sustainable use of timber resources.